Infantile melanoma: early diagnosis by total body mapping in dysplastic nevus syndrome - Priscila Neri Lacerda; Maria Estela Bellini Ribeiro; Izabelle Ferreira da Silva Mazeto; Vinícius de Souza; Hélio Amante Miot (Sociedade Brasileira de Dermatologia (SBD), 2021)
Melanoma is a rare neoplasm in the pediatric population, and it is even rarer in children under 10 years of age. Total body mapping constitutes a low-cost and non-invasive method that increases diagnostic accuracy in evaluating pigmented lesions, especially in high-risk patients. We reported the case of a 9-year boy with dysplastic nevus syndrome, in which one lesion presented a subtle change (asymmetry of structures) within a 6-months follow-up. Its excision resulted in melanoma with a Breslow thickness of 1 mm and a negative sentinel lymph node. Total body mapping reduces the number of unnecessary excisions. It allows diagnosis of melanomas in early and potentially curable stages, especially in children and patients with risk factors such as dysplastic nevus syndrome. We report this case due to the rarity of the neoplasia in this age group and also to demonstrate the importance of sequential digital dermoscopy in early diagnosis of melanoma in this population.